Preparation of Wheat-Straw-Fiber-Based Degradable Mulch Film for Sustained Release of Carbendazim and Its Application for Soybean Root Rot Control - Shuang Liu; Zhe Jin; Pengfei Zhou; Huimin Shang; Haiyan Yang; Longhai Li; Rui Li; Ying Zhang; Haitao Chen (Agronomy)
In order to sustain control over soybean root rot, wheat-straw-fiber-based mulch film (WFM) coated with carbendazim (C) and chitosan (CS) mixture (C-CS-WFM) were prepared through bar coating technology. The Box–Behnken design method was employed to investigate the effects of chitosan concentration, wet film thickness, and carbendazim loading on the dry tensile strength (DTS), wet tensile strength (WTS), and air permeance (AP) of C-CS-WFM. Eventually, the optimization process parameters were determined as follows: a chitosan concentration of 1.83–2.39%, a wet film thickness of 18–24 μm, and a carbendazim loading of 0.05–0.12 g/m2. These parameters achieved the desired physical properties of C-CS-WFM, i.e., the DTS is not less than 3.5 kN/m, the WTS is not less than 0.8 kN/m, and the AP does not exceed 2.1 μm/(Pa·s). The results showed that after the introduction of the C-CS coating, the DTS and WTS of C-CS-WFM were enhanced by 11.4% and 14.9%, respectively. In contrast, the AP was reduced by 15.6%. FT-IR analysis indicated that carbendazim was embedded in the C-CS composite material without any chemical interaction. Through SEM and sustained-release kinetic analysis, it was found that the sustained-release mechanism of C-CS-WFM conformed to the Ritger–Peppas kinetic model, and its release mechanism was the physical diffusion and matrix erosion. The results of the in vitro antifungal test and pot experiment demonstrated that C-CS-WFM could effectively inhibit the growth of Fusarium solani and promote the growth of plants. This study provided new ideas for the comprehensive prevention and control of soybean root rot.